Recurrent seizures in non-diabetic patient presenting with hypoglycemia: an eye opener for clinicians - Swati; Anushka Garg; Aryan Deol; Sheetal; Ravi Kant (International Journal of Advances in Medicine, 2026)
Seizures represent transient episodes of abnormal, excessive, and synchronized electrical discharges of neurons in the brain that may be associated with various structural, metabolic, infectious, toxic, autoimmune, or genetic conditions. Metabolic disorders also include hypoglycemia which is recognized as one of the possible seizure triggers, since reduced glucose levels hinder energy metabolism in the brain resulting in neuronal dysfunction and hyperexcitability. Therefore, estimation of blood glucose should be included in the initial approach when dealing with patients experiencing acute seizures. The opposite condition-hypoglycemia caused by seizures-is very uncommon but still exists. Despite the fact that the decrease in blood glucose may appear after prolonged generalized tonic-clonic seizures as a result of increased glucose uptake by the brain and muscles, recurrent hypoglycemia after seizure termination is quite rare, especially in the absence of diabetes mellitus. Potential mechanisms of hypoglycemia development in such cases are related to increased metabolic needs during the seizure, decreased glycogen storage in the liver, decreased gluconeogenesis and in rare cases, exaggerated insulin production.